Helminth parasites of the levantine frog (Pelophylax bedriagae Camerano, 1882) from the western part of Turkey - Demır S.; Yakar O.; Yildirimhan H. S.; Bırlık S. (Helminthologia, 2015)
Fifty-four Pelophylax bedriagae (Levantine Frog) from Turkey (İzmir and Manisa Provinces) were examined for helminth parasites. The frogs were collected between 2012 and 2014 years. Eight species of helminth parasites were recorded: 3 species of Nematoda (Rhabdias bufonis, Cosmocerca ornata, Oswaldocruzia filiformis), 3 species of Digenea (Diplodiscus subclavatus, Haematoloechus bre-viansa, Gorgoderina vitelliloba), 1 species of Acanthocephala (Acanthocephalus ranae) and 1 species of Hirudinea (Hirudo medicinalis). Pelophylax bedriagae is a new host record for these parasite species.